Analysis of gold nanospheres, nano ellipsoids, nanorods, and effect of core–shell structures for hyperthermia treatment. Issue 15 (24th March 2022) - Abbas, Ghulam; Maqbool, Saba; Shahzad, Muhammad Khuram; Afzaal, Muhammad; Daud, Muhammad Usama; Fatima, Nazma Goher; Ghuffar, Abdul
Abstract : Hyperthermia (HT) is a technique for treating malignancies by raising the temperature of the defected tissues. Abstract : Hyperthermia (HT) is a technique for treating malignancies by raising the temperature of the defected tissues. This technique has been used as a treatment to raise tumor area temperatures between 42 °C to 48 °C. Hyperthermia penetrates deeper malignant cells by heating the region of interest when magnetic nanoparticles (MNPs) are exposed to an externally induced magnetic field of the incident wave. In this work, numerical analysis was used to examine the temporal and spatial temperature distributions within a tumor. The temperature field was analyzed using the mass transfer and diffusion theories in the interstitial tissue. A bio-heating module in COMSOL Multi-Physics was used for different types of gold nanoparticles (AuNPs) including nanorods, nanospheres, and nano-ellipsoids with different shapes. The objective of this study is to analyze the use of AuNPs for hyperthermia. The results show that AuNPs achieve a maximum temperature for Au nanorods as compared to nano ellipsoids and nanospheres. The Au NPs achieve thermal equilibrium after 0.5 μs and are effective for hyperthermia treatment. The results describe the effect of nanoparticle shape and surface coating on thermal absorption around the nanoparticle in hyperthermia. The significance of Au NPs for hyperthermia is explained. It is expected that this study will be helpful in the future for hyperthermia treatment.